Ethnoscience Studies on The Tradition of Nyaneut Kejek Tea In Cigedug Village, Garut Regency - Abdul Latip; Aristo Hardinata; Andinisa Rahmaniar (ISER (Indonesian Science Education Research), 2023)
Garut Regency is one of the regions that has gastronomic tourist destinations that have the peculiarities of Garut's typical food and beverage products. Tea plantations are one of the gastronomic potentials in Garut that can produce garut tea. Kejek tea is one of the green teas from Garut that has long been developed in Garut for generations. In this article, a literature study was conducted on the processing of kejek tea and the tradition of nyaneut tea in one of the areas in Garut Regency. Literature studies are focused on the study of people's original knowledge of kejek tea and the tradition of nyaneut tea, as well as a scientific review of these two things. The results of literature studies show that in the processing of kejek tea and nyaneut traditions there is original knowledge of the community that can be explained scientifically in science or called ethnoscience. In the processing of kejek tea and the tradition of nyaneut tea, there are values that can be taken, namely the value of social, cultural, economic, and ethnobotanical values